Tactics of antihypertensive therapy during COVID-19 pandemic - Valery I. Podzolkov ("Consilium Medicum" Publishing house, 2021)
Results of foreign and Russian studies indicate a higher mortality rate of patients with concomitant cardiovascular diseases (CVD) due to the new coronavirus infection COVID-19. It has been proven that arterial hypertension, as one of the significant risk factors for the development of concomitant cardiovascular diseases, is associated with a more severe prognosis of COVID-19. This article presents the results of modern studies and large meta-analyzes of necessity and safety of the use of blockers of the renin-angiotensin-aldosterone system in patients with arterial hypertension and COVID-19. The data of studies show that an angiotensin-converting enzyme inhibitor (ACE inhibitor) and a thiazide-like diuretic is a pathogenetically rational combination. It realizes various ways of lowering blood pressure by reducing the activity of the renin-angiotensin-aldosterone system, which is achieved by using an ACE inhibitor, and natriuresis due to diuretics. As an example, a highly effective fixed combination of drugs is considered, characterized by good tolerance, which consists of an ACE inhibitor lisinopril and a thiazide-like diuretic indapamide of prolonged action. The authors expressed the opinion that the appointment of the fixed combination drug Diroton Plus (Gedeon Richter) will contribute to effective control of blood pressure and organoprotection in conditions of increased thrombogenic and prooxidative potential, characteristic of COVID-19 both in the acute stage and within the post-COVID Syndrome.